Efeito de diferentes géis clareadores na rugosidade, topografia e permeabilidade do esmalte bovino - Mendonça, Ludmila Cavalcanti de (2008)
This study evaluated surface roughness, topography and permeability of bovine enamel, by means of profilometer and scanning electron microscope (SEM), with and without silver nitrate solution, exposed to different bleaching agents. Fifty enamel samples were randomly divided into five groups (n=10): : PC16% Carbamide Peroxide 16% - Whiteness Perfect; PH6% - Hidrogen Peroxide 6% - White Class; PH35% - Hidrogen Peroxide 35% Whiteness HP Maxx; PC37% - Carbamide Peroxide 37% - Whiteness Super and C (control) wasn´t bleached and was kept in artificial saliva. For roughness analysis was used average surface rougness (Ra) and flatness coefficient (Rku) parameters. Topography and permeability observations were realized by mean SEM. For permeability evaluation samples were immersed in 50% silver nitrate solution and analysed using backscattered electron and secondary electron mode. For the roughness (Ra) evaluation Kruskal-Wallis and Wilcoxon Signed Ranks Test was used, and showed an increased on the surface roughness in all the bleachied group. The Rku parameter suggest changes on enamel integrity. The images obtained by SEM showed changes on the enamel topography and different penetrations in the silver nitrate immersed sample in the bleached group. It was concluded that different bleaching agents can alter the topography and the enamel surface roughness and the fact of silver nitrate have entered suggests area of easy penetration by oxygen.